Risk Factors for Mortality among Patients with Pseudomonas aeruginosa Bloodstream Infections: What Is the Influence of XDR Phenotype on Outcomes? - María Milagro Montero (Journal of Clinical Medicine, 2020)
This study aimed to assess the impact of extensively drug-resistant (XDR) phenotype on mortality in Pseudomonas aeruginosa bacteremia. A retrospective cohort study was performed in a tertiary hospital from January 2000 to December 2018. All consecutive prospectively recorded P. aeruginosa bacteremia in adult patients were assessed. In this study, 382 patients were included, of which 122 (31.9%) due to XDR P. aeruginosa. Independent factors associated with 14-day mortality were as follows: high-risk source of bacteremia (hazard ratio (HR) 3.07, 95% confidence interval (CI), 1.73−5.46), septic shock (HR 1.75, 95% CI, 1.12−2.75), and higher Pitt scores (one-point increments; HR 1.25, 95% CI, 1.12−1.38). Otherwise, the appropriateness of definitive antibiotic therapy was a protective factor (HR 0.39, 95% CI, 0.24−0.62). The same variables were also associated with 30-day mortality. XDR phenotype was not associated with 14- or 30-day mortality. In a subanalysis considering only high-risk source cases, combined antimicrobial therapy was independently associated with 14-day favorable outcome (HR 0.56, 95% CI, 0.33−0.93). In conclusion, XDR phenotype was not associated with poor prognosis in patients with P. aeruginosa bacteremia in our cohort. However, source of infection, clinical severity, and inappropriate definitive antibiotic therapy were risk factors for mortality. Combined antimicrobial therapy should be considered for high-risk sources.